2011
DOI: 10.2486/indhealth.ms1222
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Menopausal Hot Flashes on Mental Workload

Abstract: This study examined the differences in psychophysiological responses during mental task performance between women with (Group S) and without (Group A) menopausal hot flashes. Twelve women who reported experiencing daily moderate or severe menopausal hot flashes (Group S) and twelve women who reported having no hot flashes (Group A) participated in a mental arithmetic (Task) and a control (Non-task) experiment that occurred twice during 30 min. Although Group S experienced frequent hot flashes during mental ari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Many also have mood disturbances, although the link with menopause is less clear (1; 6; 7; 11-16) . These symptoms can be severe enough to negatively impact quality of life, work performance, and personal relationships (1; 17-20) . Current treatments for menopause-related symptoms, such as menopausal hormone therapy, antidepressants, and anticonvulsants, may have significant side effects and serious long-term adverse consequences (21-23) .…”
Section: Introductionmentioning
confidence: 99%
“…Many also have mood disturbances, although the link with menopause is less clear (1; 6; 7; 11-16) . These symptoms can be severe enough to negatively impact quality of life, work performance, and personal relationships (1; 17-20) . Current treatments for menopause-related symptoms, such as menopausal hormone therapy, antidepressants, and anticonvulsants, may have significant side effects and serious long-term adverse consequences (21-23) .…”
Section: Introductionmentioning
confidence: 99%
“…This has been done recently by Geukes et al, who studied healthy working women, representative of the Dutch female population, and showed that women’s physical and psychological menopausal complaints were associated with lower work ability, which increased the possibility of sickness absence [ 7 ]. The authors concluded that the women had a relatively low level of vasomotor symptoms (VMS) and that these complaints did not negatively impact on their work ability (see also [ 47 ]). More recently however, other researchers reported that VMS were the most frequently reported complaints with a negative effect on work [ 6 ].…”
Section: Menopause and Work Abilitymentioning
confidence: 99%
“…For example, Gartoulla et al's (2016) survey of Australian women finds those describing their work ability as poor to moderate reporting hot flushes and night sweats much more frequently than those rating their work ability at higher levels. Work can also exacerbate symptoms: e.g., stress caused by formal meetings, deadlines and training and development might increase the frequency of hot flushes (Griffiths et al, 2006;Park et al, 2008Park et al, , 2011Paul, 2003;Putnam & Bochantin, 2009;Reynolds, 1999). Mid-life menopausal bodies, prone as they may be to flushing and sweating, psychological fluctuations and erratic and heavy periods inter alia, can therefore cause problems for women at work.…”
Section: Introductionmentioning
confidence: 99%